Risk of ovarian cancer in relation to use of phenolphthalein-containing laxatives - Cooper, G S (Nature Publishing Group, 2000)
We examined ovarian cancer risk in relation to use of phenolphthalein-containing laxatives in 410 epithelial ovarian cancer cases and 713 controls. Compared to women who never used a laxative, ever use of a phenolphthalein-containing laxative was not associated with an increased risk of ovarian cancer (odds ratio, OR, 1.1, 95% confidence interval, CI, 0.9–1.4). Risk was slightly, but not significantly, higher with more frequent use (OR 1.2 for 75 or more days of use). When women who used non-phenolphthalein containing laxatives was used as the reference group, the associations were slightly, but not significantly larger (OR 1.4 for any use of phenolphthalein-containing laxatives and OR 1.5 for 75 or more days of use) © 2000 Cancer Research Campaign